2021
DOI: 10.1139/facets-2021-0096
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on the learning and achievement of vulnerable Canadian children and youth

Abstract: Many children and youth in Canada are identified as vulnerable due to educational, environmental, and social factors. They are more likely to be negatively affected by events that cause significant upheaval in daily life. The changes imposed by COVID-19, such as physical distancing, school closures, and reductions in community-based services all have the potential to weaken the systems of support necessary for these children to learn and develop. Existing inequities in educational outcomes experienced by vulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 64 publications
1
44
0
4
Order By: Relevance
“…Capturing the full range of experiences and attitudes about socialization during the pandemic will require research with a broader, more representative sample. It has been shown that children and adolescents who are more vulnerable (socially, environmentally or educationally) are more likely to experience negative impacts related to the COVID‐19 pandemic and associated measures (school closures among others) (Whitley et al, 2021 ). Families from lower socio‐economic backgrounds may have limited access to computers, Internet, books and have less time and fewer resources to face pandemic‐related stressors such as loss of employment and home schooling (Masonbrink & Hurley, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Capturing the full range of experiences and attitudes about socialization during the pandemic will require research with a broader, more representative sample. It has been shown that children and adolescents who are more vulnerable (socially, environmentally or educationally) are more likely to experience negative impacts related to the COVID‐19 pandemic and associated measures (school closures among others) (Whitley et al, 2021 ). Families from lower socio‐economic backgrounds may have limited access to computers, Internet, books and have less time and fewer resources to face pandemic‐related stressors such as loss of employment and home schooling (Masonbrink & Hurley, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note are the disruptions in areas of skill development that are fundamental to optimal growth and wellness. Students' learning and academic achievement have been negatively affected (Davies and Aurini 2021), especially for learners who were academically vulnerable before the pandemic (Whitley et al 2021). Children and youth are now moving and playing less at school (and in their communities) than before the pandemic (McNamara 2021), which has had "immediate collateral consequences" on their development (Moore et al 2020), including their mental health (Kang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the move to online learning due to the COVID-19 pandemic made it significantly more challenging for students to meet each other and work together [20,62,64]. And even under pre-pandemic circumstances, study groups have not been equally available to all students.…”
Section: Introductionmentioning
confidence: 99%